Spectrophotometry, luminescence, and colour : science & compliance : papers presented at the second joint meeting of the UV Spectrometry Group of the UK and the Council for Optical Radiation Measurements of the USA, Rindge, New Hampshire, USA, June 20-23, 1994 - Burgess, C. (Christopher); Jones, D. G. (Dianna G.) (Analytical spectroscopy library, 1995)
This book contains papers presented at the Second Joint Meeting of the UV Spectrometry Group of the UK and the Council for Optical Radiation Measurements of the USA. Topics included are: compliance and validation in spectrophotometry, advances in spectrophotometric measurements, instrument manufacturers' approaches to compliance, advances in fluorescence techniques and advances in spectrophotometry. The balance of the conference has shifted from the 1986 mix towards more applications but once again the National Laboratories have provided an excellent update on the state-of-the-art in many areas.